2014
DOI: 10.1038/srep05282
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification of the Leptin Promoter in Diet-Induced Obese Mice and the Effects of N-3 Polyunsaturated Fatty Acids

Abstract: We report evidence of a detailed epigenetic modification of the leptin promoter and the effects of n-3 polyunsaturated fatty acids (n-3 PUFAs), which is closely associated with the leptin gene transcription in obesity. In the adipose tissue of diet induced obese (DIO) mice, methylation of the CpG island and the binding of methyl-CpG-binding domain protein 2 (MBD2) and DNA methyltransferases (DNMTs) at the leptin promoter are increased and RNA Pol II is decreased. Additionally, histones H3 and H4 are hypoacetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 37 publications
(75 reference statements)
4
71
0
Order By: Relevance
“…In animal experiments, even in isocaloric diets, leptin levels were higher in rat group fed with either the high fat diet or the high protein diet compared with those fed with the high carbohydrate diet [22]. In addition leptin and insulin concentrarions of mice with DIO were also described to be high in comparison with those of control mice [23,24]. Even under the circumstances of the elevated concentrations of leptin and insulin, both of which suppress the expression of AQP7 [15,25,26] phosphatidylinositol 3 kinase pathway, the AQP7 expression of skeletal muscles of mice with DIO was up-regulated in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, even in isocaloric diets, leptin levels were higher in rat group fed with either the high fat diet or the high protein diet compared with those fed with the high carbohydrate diet [22]. In addition leptin and insulin concentrarions of mice with DIO were also described to be high in comparison with those of control mice [23,24]. Even under the circumstances of the elevated concentrations of leptin and insulin, both of which suppress the expression of AQP7 [15,25,26] phosphatidylinositol 3 kinase pathway, the AQP7 expression of skeletal muscles of mice with DIO was up-regulated in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that DNA methylation of the leptin promoter varied with obesity. In the adipose tissue of diet induced obese (DIO) mice, the methylated fraction of the leptin promoter was decreased by feeding a high-fat diet at the initial stage; however, it increased after 12 weeks of feeding a high-fat diet compared to control and low-fat diet mice [77]. In peripheral blood samples from human obese adolescents, methylation of the LEP promoter was shown to be negatively associated with BMI [78].…”
Section: Epigenetic Regulation Of Leptin-related Signalling Pathways:mentioning
confidence: 98%
“…It is believed that histone modifications serve a feedback mechanism to keep leptin levels somewhat constant within a normal range. In addition, n-3 polyunsaturated fatty acids (n-3 PUFAs) may counter adiposity via epigenetic regulation of leptin including histone modifications (Shen et al, 2014). Moreover, mitogen-activated protein kinase phosphatase 3 (MKP-3) may exert a pivotal role in obesity-induced hyperglycemia through facilitating hepatic glucose output.…”
Section: Role Of Histone Modification In Obesogenesis and Cardiomyopathymentioning
confidence: 99%